CAF-derived exosomal WEE2-AS1 facilitates colorectal cancer progression via promoting degradation of MOB1A to inhibit the Hippo pathway - Yang, Peng; Zhang, Dongsheng; Wang, Tuo; Ji, Jiangzhou; Jin, Chi; Peng, Chaofan; Tan, Yuqian; Zhou, Jiahui; Wang, Lu; Feng, Yifei; Sun, Yueming (Cell death & disease, 2022)
Cancer-associated fibroblasts (CAFs) are the most abundant stromal components in the tumor microenvironment (TME) and closely involved in tumor progression. However, the precise biological functions and molecular mechanisms of CAFs in the TME have yet to be understood. Here, we demonstrate that WEE2-AS1 is highly expressed in the CAF-derived small extracellular vesicles (sEVs). Moreover, WEE2-AS1 is markedly higher in plasma sEVs of CRC patients than in healthy subjects and its high level predicts advanced pathological staging and poor survival. Then, we conducted a series of in vitro and in vivo experiments. Elevated expression of WEE2-AS1 in sEVs increases CRC cell proliferation in vitro. Importantly, aberrant CAF-sEVs WEE2-AS1 leads to tumor formation and progression in BALB/c nude mice and promotes AOM/DSS-induced tumorigenesis. Mechanistically, WEE2-AS1 functions as a modular scaffold for the MOB1A and E3 ubiquitin-protein ligase praja2 complexes, leading to MOB1A degradation via the ubiquitin-proteasome pathway. The Hippo pathway is then inhibited and more YAP are transported into the nucleus, where they activate downstream gene transcription. Together, our data reveal that CAF-sEVs WEE2-AS1 interacts with MOB1A, promotes degradation of MOB1A, inhibits the Hippo pathway, and facilitates the growth of CRC cells. Hence, exosomal WEE2-AS1 may be a promising therapeutic target and circulating biomarker for CRC diagnosis and prognosis.